The potential value of Notch1 and DLL1 in the diagnosis and prognosis of patients with active TB - Xie, Jinling; Chen, Yinzhong; Chen, Shihao; Long, Huaquan; Zhang, Weijian; Liu, Guoan (Frontiers in Immunology, 2023)
Objectives The Notch signaling pathway has been implicated in the pathogenesis of active tuberculosis (TB), and Th1-type cell-mediated immunity is essential for effective control of mycobacterial infection. However, it remains unclear whether Notch signaling molecules (Notch1, DLL1, and Hes1) and Th1-type factors (T-bet and IFN-γ) can serve as biomarkers for tracking the progression of active TB at different stages along with peripheral blood white blood cell (WBC) parameters. Methods A total of 60 participants were enrolled in the study, including 37 confirmed TB patients (mild (n=17), moderate/severe (n=20)) and 23 healthy controls. The mRNA expression of Notch1, DLL1, Hes1, T-bet and IFN-γ in the peripheral blood mononuclear cells (PBMCs) of the subjects was measured by RT-qPCR, then analyzed for differences. Receiver Operating Characteristic curve (ROC) was used to assess the effectiveness of each factor as a biomarker in identifying lung injury. Results We found that mRNA expression levels of Notch1, DLL1, and Hes1 were upregulated in active TB patients, with higher levels observed in those with moderate/severe TB than those with mild TB or without TB. In contrast, mRNA levels of T-bet and IFN-γ were downregulated and significantly lower in mild and moderate/severe cases. Furthermore, the combiROC analysis of IFN-γ and the percentage of lymphocytes (L%) among WBC parameters showed superior discriminatory ability compared to other factors for identifying individuals with active TB versus healthy individuals. Notably, Notch pathway molecules were more effective than Th1-type factors and WBC parameters in differentiating mild and moderate/severe cases of active TB, particularly in the combiROC model that included Notch1 and Hes1. Conclusions Our study demonstrated that Notch1, Hes1, IFN-γ, and L% can be used as biomarkers to identify different stages of active TB patients and to monitor the effectiveness of treatment.